Designer topological-single-atom catalysts with site-specific selectivity - Weibin Chen; Menghui Bao; Fanqi Meng; Bingbing Ma; Long Feng; Xuan Zhang; Zanlin Qiu; Song Gao; Ruiqin Zhong; Shibo Xi; Xiao Hai; Jiong Lu; et al. (Nature Communications)
Abstract Designing catalysts with well-defined, identical sites that achieve site-specific selectivity, and activity remains a significant challenge. In this work, we introduce a design principle of topological-single-atom catalysts (T-SACs) guided by density functional theory (DFT) and Ab initio molecular dynamics (AIMD) calculations, where metal single atoms are arranged in asymmetric configurations that electronic shield topologically misorients d orbitals, minimizing unwanted interactions between reactants and the support surface. Mn1/CeO2 catalysts, synthesized via a charge-transfer-driven approach, demonstrate superior catalytic activity and selectivity for NO x removal. A life-cycle assessment (LCA) reveals that Mn1/CeO2 significantly reduces environmental impact compared to traditional V-W-Ti catalysts. Through in-situ spectroscopic characterizations combined with DFT calculations, we elucidate detailed reaction mechanisms. This study establishes T-SACs as a promising class of catalysts, offering a systematic framework to address catalytic challenges by defining site characteristics. The concept highlights their potential for advancing selective catalytic processes and promoting sustainable technologies.